The Impact of Patient-Centered Care at Work: make a Difference to the Patient Experience (The International Journal for Scientific Research, 2022)
Patient-centered care is a cornerstone of modern healthcare, prioritizing individual needs and fostering collaborative partnerships between patients and providers. This systematic review examines the role of multidisciplinary teams in enhancing patient experience and satisfaction within patient-centered care paradigms, aiming to identify best practices for optimizing healthcare delivery. This systematic review explores real-life examples of multidisciplinary team (MDT) approaches to patient-centered care, examining interventions and outcomes across diverse healthcare settings to enhance patient experience and satisfaction. Assessing patient experience and satisfaction outcomes following multidisciplinary team (MDT) interventions is crucial for evaluating healthcare effectiveness. This review highlights methodologies and findings from studies utilizing validated tools to measure patient-reported outcomes. Patient-centered care, driven by multidisciplinary teams (MDTs), revolutionizes healthcare delivery by prioritizing collaboration and empathy. Through this review, we explore MDTs' profound impact on patient-centered care and strategies for optimizing outcomes.
Keywords: Patient-Centered Care; Multidisciplinary; Teams; Patient; Experience; Satisfaction